Paralinguistic Aspect of Commercial Advertising on Television - Meli Agustin; Dewi Rosaria Indah (Merwin Publisher, 2023)
This study aims to analyze the paralinguistic aspects of commercial advertising through television media. How important is the paralinguistic aspect in an advertisement, resulting in the conclusion that paralinguistics does not only affect verbal and direct communication, but also communication in the media. In this study, the research is advertising through television media. This study uses a qualitative descriptive method. The source used in this research is the narrative of the conversation in the advertisement. The three commercial advertisements that will be examined in paralinguistic aspects are “Keanu's version of Pentene, Kenyataan yang menyegarkan’s version of Sprites, Indomie Goreng Rica-rica” The success of delivering messages through the media is the main goal of advertising, the communicator aspect in conveying messages is an important sensor in it. Verbal or paralinguistic communication messages are references so that a communicator can look attractive in building perceptions of the advertising image that will be displayed. Keywords: Paralinguistic, nonverbal communication, commercial advertising